Increased Maternal Prenatal Adiposity, Inflammation, and Lower Omega-3 Fatty Acid Levels Influence Child Negative Affect - Gustafsson, Hanna C.; Holton, Kathleen F.; Anderson, Ashley N.; Nousen, Elizabeth K.; Sullivan, Ceri A.; Loftis, Jennifer M.; Nigg, Joel T.; Sullivan, Elinor L. (Frontiers in Neuroscience, 2019)
Objective: Increased maternal adiposity during pregnancy is associated with offspring risk for psychiatric disorders. Inflammation secondary to adiposity is believed to be an important mechanism through which this effect occurs. Although increased adiposity introduces risk, not all children of overweight mothers develop these problems. Gestational factors that modify this risk are not well understood. If maternal increased adiposity exerts its effects on offspring outcomes by increasing inflammation in the gestational environment, then anti-inflammatory inputs such as omega-3 fatty acids may be one protective factor. The goal of this study was to investigate whether maternal pre-pregnancy Body Mass Index (BMI) and omega-3 fatty acid levels independently and/or interactively predicted offspring infant negative affect, an early life marker of risk for psychopathology. Methods: Data came from a prospective study of women recruited during pregnancy and their 6 month old infants (N=62; 40% female). Maternal pre-pregnancy BMI was pulled from medical charts and third trimester omega-3 fatty acid concentrations were assessed in plasma. Child negative affect was assessed using observer- and maternal-ratings at age 6 months. Maternal inflammation was indexed by third trimester plasma levels of interleukin-6, tumor necrosis factor-alpha, and monocyte chemoattractant protein-1. Results: Maternal pre-pregnancy BMI was associated with increased infant negative affect whereas eicosapentaenoic acid was associated with less infant negative affect. Maternal omega-3 fatty acid levels moderated the effect of BMI on infant negative affect, such that omega-3 fatty acids buffered children against the negative consequences of increased adiposity. Supporting the role of maternal inflammation in these associations, maternal BMI and omega-3 fatty acid levels interacted to predict maternal third trimester inflammation. Further, maternal inflammation was associated with increased infant negative affect. Conclusions: Results suggest that omega-3 supplementation during pregnancy may protect against offspring behavioral risk associated with increased maternal adiposity.